IL-40: A New B Cell-Associated Cytokine Up-Regulated in Rheumatoid Arthritis Decreases Following the Rituximab Therapy and Correlates With Disease Activity, Autoantibodies, and NETosis - Navrátilová, Adela; Andrés Cerezo, Lucie; Hulejová, Hana; Bečvář, Viktor; Tomčík, Michal; Komarc, Martin; Veigl, David; Tegzová, Dana; Závada, Jakub; Olejárová, Marta; Pavelka, Karel; Vencovský, Jiří; et al. (Frontiers in Immunology, 2021)
Background: Interleukin 40 (IL-40) is a newly identified B cell-associated cytokine implicated in humoral immune responses and B cell homeostasis. As B cells play a pivotal role in autoimmunity, we investigated the function of IL-40 in rheumatoid arthritis (RA). Methods: IL-40 expression was determined in the synovial tissue from RA and osteoarthritis (OA) patients. IL-40 was analysed in the serum/synovial fluid of patients with RA (n=50), systemic lupus erythematosus (SLE, n=69), OA (n=44), and healthy controls (HC, n=50). We assessed the changes of IL-40 levels in RA patients following the B cell depletion by rituximab (n=29) or after the TNF inhibition by adalimumab (n=25). We examined the relationship between IL-40, disease activity, autoantibodies, cytokines, and NETosis markers. Effect of IL-40 on synovial fibroblasts was determined. Results: IL-40 was overexpressed in RA synovial tissue, particularly by synovial lining and infiltrating immune cells. The levels of IL-40 were up-regulated in the synovial fluid of RA versus OA patients (p<0.0001). Similarly, IL-40 was increased in the serum of RA patients compared to HC, OA, or SLE (p<0.0001 for all) and decreased after 16 and 24 weeks (p<0.01 and p<0.01) following rituximab treatment. No significant effect of adalimumab on IL-40 was observed. IL-40 levels in RA patients correlated with rheumatoid factor-IgM and anti-cyclic citrullinated peptides (anti-CCP) in the serum (p<0.0001 and p<0.01), as well as in the synovial fluid (p<0.0001 and p<0.001). Synovial fluid IL-40 was also associated with disease activity score DAS28 (p<0.05), synovial fluid leukocyte count (p<0.01), neutrophil attractants IL-8 (p<0.01), MIP-1α (p<0.01), and markers of neutrophil extracellular traps externalization (NETosis) such as proteinase 3 (p<0.0001) and neutrophil elastase (p<0.0001). Synovial fibroblasts exposed to IL-40 increased the secretion of IL-8 (p<0.01), MCP-1 (p<0.05), and MMP-13 (p<0.01) compared to the unstimulated cells. Conclusions: We show the up-regulation of IL-40 in RA and its decrease following B cell depleting therapy. The association of IL-40 with autoantibodies, chemokines, and markers of NETosis may imply its potential involvement in RA development. Moreover, IL-40 up-regulates the secretion of chemokines and MMP-13 in synovial fibroblasts, indicating its role in the regulation of inflammation and tissue destruction in RA.